2016
DOI: 10.1038/srep35734
|View full text |Cite
|
Sign up to set email alerts
|

3D texture analysis for classification of second harmonic generation images of human ovarian cancer

Abstract: Remodeling of the collagen architecture in the extracellular matrix (ECM) has been implicated in ovarian cancer. To quantify these alterations we implemented a form of 3D texture analysis to delineate the fibrillar morphology observed in 3D Second Harmonic Generation (SHG) microscopy image data of normal (1) and high risk (2) ovarian stroma, benign ovarian tumors (3), low grade (4) and high grade (5) serous tumors, and endometrioid tumors (6). We developed a tailored set of 3D filters which extract textural fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…For example, the dermis and ovarian stroma in normal tissues have 3D mesh-like morphologies [9,10], and SHG will not visualize the entire structure. We previously have shown that 3D texture analysis provides significantly improved discrimination between ovarian tumors over the analogous 2D approach even using the incomplete information in 3D stacks [8]. Similar results were found by Georgakoudi and co-workers using a different image analysis approach [11].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…For example, the dermis and ovarian stroma in normal tissues have 3D mesh-like morphologies [9,10], and SHG will not visualize the entire structure. We previously have shown that 3D texture analysis provides significantly improved discrimination between ovarian tumors over the analogous 2D approach even using the incomplete information in 3D stacks [8]. Similar results were found by Georgakoudi and co-workers using a different image analysis approach [11].…”
Section: Introductionsupporting
confidence: 75%
“…Using these types of metrics, SHG imaging has been used for revealing extracellular matrix (ECM) structural changes in a wide range of diseases such as cancers, connective tissue disorders, and fibroses [27]. For example, we have shown that different ovarian tumors are morphologically distinct from normal tissues, as well as benign tumors and tissues at high risk for developing high grade cancer [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer accounts for only 4% of malignant tumors in women, but it has the highest mortality rate among all gynecological malignant tumor types (3,4). Recurrence and early metastasis of tumor cells are the primary reasons for the poor prognosis of patients with ovarian cancer (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the approach was generalized to 3-D texture analysis and to classify SHG images from six different ovarian tissue types. 14 These studies demonstrate the potential of machine learning-based evaluation of SHG images for improved diagnostic accuracy of ovarian cancer detection.…”
Section: Introductionmentioning
confidence: 72%